2023
DOI: 10.3390/ijms242115654
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approach Targeting Gut Microbiome in Gastrointestinal Infectious Diseases

Ziying Han,
Yiyang Min,
Ke Pang
et al.

Abstract: While emerging evidence highlights the significance of gut microbiome in gastrointestinal infectious diseases, treatments like Fecal Microbiota Transplantation (FMT) and probiotics are gaining popularity, especially for diarrhea patients. However, the specific role of the gut microbiome in different gastrointestinal infectious diseases remains uncertain. There is no consensus on whether gut modulation therapy is universally effective for all such infections. In this comprehensive review, we examine recent deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…More research is required to determine the effect of bacterial diversity on ARLD, and to what extent treatment with beneficial microorganisms could alleviate symptoms. Repair of the gut barrier is possible with microbial fecal transplants (MFTs), supplementation with SCFAs, and synthetic biology interventions [69]. Despite all the knowledge gathered on ARLD, we still lack a detailed understanding of which species are more prone to cause a leaky gut, the species or strains best suited to rectify damage to the gut wall, and the most harmful circulating PAMPs.…”
Section: Alcohol-related Liver Disease (Arld)mentioning
confidence: 99%
“…More research is required to determine the effect of bacterial diversity on ARLD, and to what extent treatment with beneficial microorganisms could alleviate symptoms. Repair of the gut barrier is possible with microbial fecal transplants (MFTs), supplementation with SCFAs, and synthetic biology interventions [69]. Despite all the knowledge gathered on ARLD, we still lack a detailed understanding of which species are more prone to cause a leaky gut, the species or strains best suited to rectify damage to the gut wall, and the most harmful circulating PAMPs.…”
Section: Alcohol-related Liver Disease (Arld)mentioning
confidence: 99%
“…This triggers mucosal inflammatory reactions, impairing the secretory function of secretory immunoglobulin A through the inherent layer of the mucosa, thereby compromising the intestinal immune barrier ( Zyrek et al., 2007 ; Jones and Versalovic, 2009 ). Studies have shown that when the intestinal environment is disrupted, various active substances released by pathogenic bacteria and their antigens can cause gastrointestinal diseases ( Han et al., 2023 ). Gut microbiota dysbiosis can affect the metabolism of substances, such as choline and bile acids, as well as energy absorption, thereby leading to metabolic diseases, such as obesity and diabetes ( Janssen and Kersten, 2015 ).…”
Section: Introductionmentioning
confidence: 99%